Hubungan antara Adiksi Internet dengan Prestasi Belajar pada Siswa Kelas XII SMK Teknologi Nasional Palembang - Melsy Kurnia; Sarah Afifah (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine the relationship between internet addiction and learning achievement. The research method is correlational quantitative. The research subjects were 81 students of class XII who were selected by cluster random technique. The research instrument used was the internet addiction scale and the report cards of XII grade student’s. The results of the analysis using Spearman Rank with the help of SPSS version 22 for windows showed that there was a relationship between internet addiction and learning achievement, with a significance value (0.006 <0.05), r = -0.302 and a fairly or strong enough level of correlation strength. The direction of the relationship between the variables of internet addiction and learning achievement is negative.